FORMATTIVE EVALUATION IS AN UNINTERRUPTABLE PART OF THE TRAINING PROCESS ON LESSONS OF CHEMISTRY - A.D. Kalimukasheva; D.Z. Kalimanova; Z.A. Imankulova (Academic Scientific Journal of Chemistry, 2022)
In recent years, the world pedagogy is in the process of rethinking the system for assessing students’ learning achievements, since evaluation is one of the main stages of the educational process. One of the goals of the school is to create conditions conducive to the pursuit of self-education, self-knowledge of the individual, the development of motivation to achieve success, that is, the formation of key competencies of students. According to the State Program for the Development of Education in the Republic of Kazakhstan for 2011-2020, when evaluating students’ learning achievements it is important to focus on the process of developing the key competencies of the future specialist. And for this it is necessary to make significant changes to the traditional system of knowledge assessment.